Subterranean river captures in siliciclastic rocks in a semiarid climate: the case of the Poti River Canyon, Brazilian Northeast - Rodrigues, Wesley Feitosa; Maia, Rubson Pinheiro; Silva, Helena Vanessa Maria da; Salgado, André Augusto Rodrigues (Revista Brasileira de Geomorfologia, 2024)
This research investigates a possible subterranean river capture responsible for the morphogenesis of the Poti River Canyon, which crosses the uplifted edge of the Parnaíba Basin, in the northern Northeast of Brazil. Morphological and lithostructural evidence of river captures was analysed using remote sensing products (e.g., drainage network, topography, paleotopography, structural framework) and field expeditions. The results indicated a sudden inflexion of the upper course of the Poti River, low and anomalous divides in the local geomorphological context, canyon with valley segments exhibiting asynchronous morphologies, and block collapse controlled by dissolution along fracture networks. Given this set of data, we propose an evolutionary model of subterranean river capture for the formation of the Poti River canyon, which, through paleotopographic modelling, was linked to the Pleistocene epoch. This drainage rearrangement would have been influenced by a Neogene-Quaternary morphogenetic framework of structural reactivations, regional uplift, and climatic oscillations. On this basis, it was concluded that epigenetic processes were significant for a drainage rearrangement of approximately 10,540 km² of areas in a semiarid region with sandstone substrate.